Entangled in the Net? Would Scandals function under the Conditions of the Internet alone? - SJ, Johannes Ehrat (Žurnalistikos tyrimai, 2011)
Using semiotic method of consideration the article investigates judgement power of public sphere in traditional media and internet. The analysis reminds that news stories obey the narrative rules. They become an object for judgement only in a mediation that allows present public opinion. At the same time because of mediation and in accordance with functioning of meta-texts these stories become subject of moralising sanction to their heroes. For mass media, the mediation function creates the parallel universe of the public sphere. The aim of the article is to find an answer whether there exists something in the internet which produces a similar public universe.Theoretical argument lets to conclude that the tribunal of public opinion is not just a meaning apparatus; it also has to be narrated. That means, that the question of justice, of right or wrong, has to be turned into a pragmatic question of performance (how well?) and competence (by whom?). As publicity is only an idea, a meaning apparatus, for normative purposes need to hide behind narrative plausibility. As soon as actors are seen as pragmatic subjects, they are subject to sanctioning. Actually, a source is the direct will of the judging instance, which in the public sphere is the hypostasis of ‘all’.When internet lacks direct mediation instance, it is unable to turn information into narratives. Without public sphere produced by traditional media the internet lacks the meaning. Such stating together with the example of Wikileaks let to conclude that when there is no legitimisation of power, then, no realisation of the pragmatic subject, and in consequence – there is no scandal.Keywords: common sense, industrial meaning, internet communication, judgement, meta-text, meaning, meaning constraint, moralising, narrative, power (meta-text 1), pragmatic subject (meta-text 2), publicity, public opinion, public sanctioning, scandal, theatre meaning.